Osadnictwo wczesnośredniowieczne nad Jeziorem Wojnowickim - Jankowska, Dobrochna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
The article aims to present the results of rescue excavations of Early Medieval sites located in the area of the planned reservoir „Wonieść” (Great Poland) and carried out in the years 1976–1980. In particular, the results of excavations of remains of a metallurgical settlement at Wojnowice 2, Osieczna commune, are discussed.
The Early Medieval settlements at the Wojnowice Lake